The outcome of transpelvic magnetic stimulation (TPMS) in treating women with urinary incontinence and overactive bladder : a prospective observational study - Nusee, Zalina; Ismail, Rozihan; Karim, Nazura; Ismail, Hamizah; Mohd Rus, Razman (2017)
Pelvic floor muscle therapy (PFMT) is the simplest said to be and the most effective treatment for lower urinary tract dysfunction (LUTs) if it is done properly in a motivated women.